"Builders of a New Social Bond": Fratelli Tutti on Good Politics and the Challenge of Inequality. (7th November 2021) - Mulligan, Suzanne
Abstract: This article examines Pope Francis's political vision as outlined in Fratelli Tutti, and argues that inequality presents a challenge to achieving what he calls "good politics." Political trust is being eroded throughout the world due to corruption and rising economic disparities, with potentially damaging consequences for democratic politics. Inequality contributes to political instability since it weakens the common good, social solidarity, and critical citizenship. The social doctrine of the Catholic Church provides the context from which various forms of inequality will be examined, with particular focus on Fratelli Tutti .